Hermeneutics and Argumentation: Contributions for the Understanding of Intercultural Dialogue - Hidalgo Nieto, Catalina (Estudios de Filosofía, 2016)
In today’s pluralistic societies, the meeting of heterogeneous rationalities has led to the emergence of intercultural conflicts, whose solution is usually expected from intercultural dialogue spaces. In these spaces, dialogue’s argumentative dimension is fundamental, for the parts in conflict have the leading role in a reason exchange with a communicative aim. Nevertheless, since it’s an intercultural dialogue, the argumentative dimension is insufficient for it does not offer the necessary lineaments to understand arguments justified by a rationality different from its own. As a result, intercultural dialogue needs a hermeneutic dimension, which should exhibit how the dialogical encounter of heterogeneous rationalities helps to expand the comprehension processes of the parties, and so, establishing the dialogical base required for the construction of a pluralist society.